Outsourcing de software: Variables críticas en el proceso de toma de decisiones (Software outsourcing: Variables involved in decision making) - Palomo González, Miguel Ángel; Cantú, José (Facultad de Contaduría Pública y Administración U.A.N.L., 2009)
Abstract. The Software Outsourcing has become a solution for organizations or businesses, due to various reasons or variables that range from reducing costs to keep their technology updated. Outsourcing is defined as business processes that are performed by an organization (Supplier) establishes a contractual relationship (Costumer-Supplier) and is given the responsibility for execution of business processes to the supplier. Based on the significant investment in imports generated by companies in Mexico, it was performed a literature review to identify the key variables that, in principle, influence the decision to turn to Software Outsourcing and, at the end, we propose a Software Outsourcing Model.